MANAJEMEN WISATA RELIGI SULTAN SYARIF ABDURRAHMAN AL-QADRI KALIMANTAN BARAT: ANALISIS PERAWATAN DAN PROMOSI WISATA RELIGI - Waldan, Raziki; Hasanah, Uswatun (J-MD Jurnal Manajemen Dakwah, 2023)
This research is motivated by the many people who are so enthusiastic about coming on a pilgrimage to the tomb of Sultan Syarif Abdurrahman Al-Qadri in Batu Layang, Pontianak City. Increasingly, the tomb of Al-Qadri was increasing, initially it was not projected for tourism, but because many were interested, it became a tourist attraction and is continuously being expanded. However, according to the management, this cannot be said to have received sufficient attention from the government. This study uses qualitative research with a descriptive approach. The data sources in this study are primary data consisting of the Secretary of the King of the Qadriah Palace, the caretaker of the tomb, the head of the waqf, and pilgrims. While secondary data consists of institutional documents, observations, books, articles, journals, internet and social media accounts. Data collection techniques were carried out by interview, observation and documentation methods. Data analysis techniques were carried out by data reduction, data presentation and drawing conclusions. The results of the research include: 1) Planning is carried out according to needs such as: Planning to improve facilities, expand the parking area, plan funding. 2) organization includes: official letter selecting the caretaker from the agency, election of the waqf chairman, division of tasks, there is no structure but there is a clear division of labor namely: waqf chairman, secretary, treasurer, and caretaker. 3) mobilization is carried out at the stage of repairing facilities, division of labor. The mobilization was carried out by the caretaker, the mobilization was also carried out on expanding parking lots, the mobilization was carried out on order of pilgrims and their officers provided motivation, guidance and direction in carrying out the repair of facilities such as in painting, repairing cemeteries. 4) supervision is carried out by the caretaker in terms of place arrangement arrangement activities. Monitoring is also carried out by caretakers such as carrying out the expansion of the parking area. Keywords: Management, grave pilgrimage, tomb of Sultan Syarif Abudrrahman Al Qadri, religious touris